The Film Museum Practice and Film Historiography The Case of the Nederlands Filmmuseum (1946-2000) - Lameris, Bregt 1973- (Amsterdam University Press, 2017)
Rich in detail, this is a study of the interrelationships between film historical discourse and archival practices. Exploring the history of several important collections from the EYE Film Museum in Amsterdam, Bregt Lameris shows how archival films and collections always carry the historical traces of selection policies, restoration philosophies, and exhibition strategies. The result is a compelling argument that film archives can never be viewed simply as innocent or neutral sources of film history
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Okt 2018)
Keywords: Nederlands Filmmuseum; Geschichte 1946-2000; Motion pictures -- Netherlands -- History -- 20th century; Filmgeschichtsschreibung; Filmmuseum; Hochschulschrift